Development of Bioenergy from Biomass in Ukraine - Galchynska, Julia; Maciejczak, Mariusz; Orlikowskyi, Mykola (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
The paper aims to present and assess the current situation of bioenergy production in Ukraine as well as provide insights into its development in the future. It is argued that the great potential of the Ukrainian agrarian sector could ensure not only food needs, but also could become a main source of production and accumulation of bioenergy in agro ecosystems. Under this perspective it can further the increase of energy safety.